Initial Estimated Glomerular Filtration Rate Decline and Long-Term Renal Function During Intensive Antihypertensive Therapy: A Post Hoc Analysis of the SPRINT and ACCORD-BP Randomized Controlled Trials - Collard, Didier (Hypertension, 2020)
Lowering blood pressure (BP) can lead to an initial decline in estimated glomerular filtration rate (eGFR). However, there is debate how much eGFR decline is acceptable. We performed a post hoc analysis of ACCORD-BP (Action to Control Cardiovascular Risk in Diabetes-Blood Pressure) and SPRINT (Systolic Blood Pressure Intervention Trial), which randomized patients to intensive or standard systolic BP-targets. We determined the relation between initial decline in mean arterial pressure and eGFR. Subsequently, we stratified patients to BP-target and initial eGFR decrease and assessed the relation with annual eGFR decline after 1 year. A total of 13 266 patients with 41 126 eGFR measurements were analyzed. Up to 10 mm Hg of BP-lowering, eGFR did not change. Hereafter, there was a linear decrease of 3.4% eGFR (95% CI, 2.9%–3.9%) per 10 mm Hg mean arterial pressure decrease. The observed eGFR decline based on 95% of the subjects varied from 26% after 0 mm Hg to 46% with a 40 mm Hg mean arterial pressure decrease. There was no difference in eGFR slope (P=0.37) according to initial eGFR decline and BP-target, with a decrease of 1.24 (95% CI, 1.09–1.39), 1.20 (95% CI, 0.97–1.43), and 1.14 (95% CI, 0.77–1.50) in the 5%, 5% to 20%, and >20% stratum during intensive and 0.95 (95% CI, 0.81–1.09), 1.23 (95% CI, 0.97–1.49), and 1.17 (95% CI, 0.65–1.69) mL/minute per 1.73 m(2) per year during standard treatment. In patients at high cardiovascular risk with and without diabetes mellitus, we found no association between initial eGFR and annual eGFR decline during BP-lowering treatment. Our results support that an eGFR decrease up to 20% after BP lowering can be accepted and suggest that the limit can be extended up to 46% depending on the achieved BP reduction. REGISTRATION—: URL: https://www.clinicaltrials.gov; Unique identifier: NCT00000620, NCT01206062.